The bony endometrium: a rare case of osseus metaplasia of endometrium - Syed, Saman; Telugu, Jyotsna; Sameera, Shaik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Osseous metaplasia of endometrium is an uncommon condition which presents as a bone in endometrium. The pathophysiology of this condition is still not understood completely. Many theories have been formulated to explain its occurrence. Most patients with this disorder present with 2o amenorrhoea or 2o infertility. Here, we present a case of 22 years old woman presenting to us with secondary amenorrhoea. Ultrasonography showed echogenic calcified endometrium suggestive of calcification. Hysteroscopy was done which revealed bony fragments in uterine cavity, which were removed, procedure went uneventful and patient was started on oestrogen and progesterone for endometrium regeneration. Histopathology report was suggestive of osseous metaplasia of endometrium.